Impact of Pteridium aquilinum on vegetation in Nyungwe Forest, Rwanda - J.M.V. Senyanzobe (Heliyon, 2020)
Pteridium aquilinum acts as an important ecological filters in dominated communities. A study to investigate the effects of its dominance in the vegetation of Nyungwe was conducted. Sampling was done in Mubuga and Uwajerome mountains. A total of 53 alternate plots measuring 10 m × 10 m were sampled along a transect at regular interval of 10 m. In each plot, the species were identified and the cover abundance measured subjectively. Plant strategies, succession, biological forms, distribution and conservation status of each species were also determined. Data on species composition and cover abundance were analyzed using MVSP software and Shannon -Weiner index was used to determine diversity of communities. Descriptive statistics were used to assess the characteristics of the species.A total of 141 species belonging to 100 genera and 54 families and distributed in four plant communities were identified. Pteridium aquilinum, Macaranga kilimandischarica, Lycopodium clavatum and Microglossa parvifolia were dominant in communities I, II and III, with average cover of 31%, 6% and 4% respectively. The primary forest was dominated by Pavetta rwandensis and Allophyllus chaunostachys in community IV, with 21% and 10% coverage respectively. Shannon- Weiner and evenness indices were 1.538, 2.925, 3.251 and 2.940 and 0.436, 0.716, 0.791 and 0.768 in communities I, II, III and IV respectively. Species richness were 34, 36, 61 and 46 in communities I, II, III and IV respectively.Ruderal, chamaephytes, secondary, Africa tropical and least concerns plant species predominated in Pteridium vegetation areas with 76% 48%, 69%, 43% and 90% of total species respectively. Competitive, phanerophytes, primary, Afromontane and least concerns plant species dominated in non-dominated area with 54%, 52%, 58%, 40% and 88% of total species respectively.Pteridium aquilinum restricted the growth of trees as exhibited by the presence of few phanerophytes and enhanced the growth of ruderal species, both of which are indicators of disturbed forest. The tree species observed in P. aquilinum cut-areas was Macaranga kilimandischarica.